2020
DOI: 10.1007/s40262-020-00924-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics/Pharmacodynamics of Antiviral Agents Used to Treat SARS-CoV-2 and Their Potential Interaction with Drugs and Other Supportive Measures: A Comprehensive Review by the PK/PD of Anti-Infectives Study Group of the European Society of Antimicrobial Agents

Abstract: There is an urgent need to identify optimal antiviral therapies for COVID-19 caused by SARS-CoV-2. We have conducted a rapid and comprehensive review of relevant pharmacological evidence, focusing on (1) the pharmacokinetics (PK) of potential antiviral therapies; (2) coronavirus-specific pharmacodynamics (PD); (3) PK and PD interactions between proposed combination therapies; (4) pharmacology of major supportive therapies; and (5) anticipated drug-drug interactions (DDIs). We found promising in vitro evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 92 publications
(125 reference statements)
1
24
0
Order By: Relevance
“…Our most interesting finding is the promising antiviral activity of interferons, possibly due to low endogenous interferon levels induced by SARS-CoV-2 23, 24 . Interferons (alpha and beta) have shown extensive in vitro activity against Severe acute respiratory syndrome-1 (SARS-CoV-1) and Middle East respiratory syndrome coronavirus (MERS-CoV) 25, 26 .However, this has not translated into clinical effectiveness in MERS-CoV 25 , although results from one trial are still pending 27 . Although recent data suggests interferon beta may be more potent than alpha against SARS-CoV-2 in vitro 28 , possibly due to higher selective indices for interferon-beta 1b, upon finding similar effects of interferon alpha and beta in our primary analysis (Figure S3), we decided to combine the interferon effect to better explore drug combinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our most interesting finding is the promising antiviral activity of interferons, possibly due to low endogenous interferon levels induced by SARS-CoV-2 23, 24 . Interferons (alpha and beta) have shown extensive in vitro activity against Severe acute respiratory syndrome-1 (SARS-CoV-1) and Middle East respiratory syndrome coronavirus (MERS-CoV) 25, 26 .However, this has not translated into clinical effectiveness in MERS-CoV 25 , although results from one trial are still pending 27 . Although recent data suggests interferon beta may be more potent than alpha against SARS-CoV-2 in vitro 28 , possibly due to higher selective indices for interferon-beta 1b, upon finding similar effects of interferon alpha and beta in our primary analysis (Figure S3), we decided to combine the interferon effect to better explore drug combinations.…”
Section: Discussionmentioning
confidence: 99%
“…In the Cox proportional hazard analysis, consistent across data qualities and sampling site combinations, we found either a significant or trend towards significant synergistic activity of interferon plus ribavirin (Figures 3, 4, S4). An extensive body of literature exists to show both interferon alpha and beta are synergistic with ribavirin in vitro against both SARS-CoV-1 and MERS-CoV 25 . This synergy, however, was not confirmed when tested in the NLME analysis, indicating that the detected synergistic effect from the time to viral clearance analysis might be confounded.…”
Section: Discussionmentioning
confidence: 99%
“…The need for an eff ective treatment for infected patients thus looms large. The results from Randomized Controlled Trial (RCT) for remdesivir are encouraging and provide some direction for the treatment of COVID-19 patients [18]. Further to this, it is highly likely that one or more other agents mentioned in this review, in combination may emerge as a prophylactic or as an early treatment option to decrease the viral shedding, transmission, and/ or to reduce disease progression.…”
Section: Discussionmentioning
confidence: 86%
“…The available data are based on in vitro studies in various cell lines. The EC50 values for other viruses are compared against SARS-CoV-2, while EC90 is usually preferred only when the EC90 is nine-fold higher than EC50 [18].…”
Section: Pharmacokinetics/pharmacodynamics (Pk/pd) Of Combo Antiviralmentioning
confidence: 99%
“…A recent analysis of drugs proposed for repurposing as SARS-CoV-2 antiviral medicines revealed that very few of the proposed candidates achieved their target concentrations after administration of approved doses to humans [29]. Moreover, there have been several recent calls to integrate understanding of pharmacokinetic principles into COVID-19 drug prioritization[3032]. Initial assessment of the plasma pharmacokinetics of SFV indicated that the concentrations able to inhibit SARS-CoV-2 replication in vitro were unlikely to be achievable after approved doses.…”
Section: Resultsmentioning
confidence: 99%